Study of the Response and Calibration Procedures of LiF:Mg, Ti TLD-100 for the Dosimetry of Photon Beam (Bangladesh Journal of Physics, 2025)
To guarantee quality assurance and quality control of the received radiation dose and treatment level, Thermoluminescent Dosimeter (TLD) is frequently employed in personal control and monitoring equipment. TLDs are commonly used to ensure the precise delivery of radiation doses to patients in clinical radiotherapy, diagnostic radiology, personal radiation monitoring, and environmental radiation dosimetry. Even though the manufacturer made all the TLDs in the same batch, their sensitivity varies. This study aims to examine the TLD crystal calibration process, in particular, the crystal sensitivity and linearity of individual TLDs following exposure to radiation at various dosage levels for precise dosimetric radiotherapy purposes. Herein, a batch of twenty (20) LiF:Mg,Ti dosimeters was used for calibration in the air for low dose levels and in tissue equivalent water phantom for high dose. In this method, dosimetry of 20 sets of TLDs was carried out in the air on the skin of Alderson rando phantom and was exposed by 137Cs source to 1 mSv, 2 mSv, 3 mSv, 4 mSv, 5 mSv, 10 mSv, and 20 mSv dose. Again, TLDs were irradiated to 60Co beams following the reference dosimetry for 50 cGy, 100 cGy, 150 cGy, and 200 cGy at reference depth (5 cm) of a water phantom. The uncertainty of the variation of crystal sensitivity of our TLDs is 0.21%. The dose – response linearity of TLDs in both cases showed to be very close to unity having uncertainty within the recommended limit. This finding supports the clinical practice of measuring precise dosages of radiation using TLDs and essential to guarantee the correct delivery of the dose to the patient.Bangladesh Journal of Physics, Vol. 29, Issue 2, pp. 59 – 67, December 2022